2018
DOI: 10.1002/jbm.b.34250
|View full text |Cite
|
Sign up to set email alerts
|

A novel patient‐specific three‐dimensional drug delivery construct for regenerative endodontics

Abstract: for their invaluable assistance during dog surgery and histology processing, respectively. M.C.B. acknowledges the National Institutes of Health (NIH)/National Institute of Dental and Craniofacial Research (NIDCR) (Grants K08DE023552 and R01DE026578). The content is solely the responsibility of the authors and does not necessarily represent the official views of the National Institutes of Health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 41 publications
1
32
0
Order By: Relevance
“…Indeed, the TAPeluting nanofibers are able to release the antibiotics following a well-controlled scenario, with confirmed antimicrobial properties, as demonstrated by the studies included in this review. On the basis of 5 studies that reported on the use of TAP-eluting nanofibers for the disinfection of biofilm-infected dentin samples, 4 showed similar antimicrobial activity as compared with TAP 17,18,32,34 ; the other study 20 exhibited a slightly lower ability to kill bacteria (97.5%) compared with TAP (100%), although it may still be considered an excellent result. One should consider the concentration of antibiotics used to fabricate the TAP-eluting nanofibers in those studies, which ranged from 25 to 35 mg/mL, as being lower than the amount used to prepare the paste-like TAP (50 mg/mL).…”
Section: New Alternatives In the Concept Antibiotic-eluting Fibers Asmentioning
confidence: 99%
See 4 more Smart Citations
“…Indeed, the TAPeluting nanofibers are able to release the antibiotics following a well-controlled scenario, with confirmed antimicrobial properties, as demonstrated by the studies included in this review. On the basis of 5 studies that reported on the use of TAP-eluting nanofibers for the disinfection of biofilm-infected dentin samples, 4 showed similar antimicrobial activity as compared with TAP 17,18,32,34 ; the other study 20 exhibited a slightly lower ability to kill bacteria (97.5%) compared with TAP (100%), although it may still be considered an excellent result. One should consider the concentration of antibiotics used to fabricate the TAP-eluting nanofibers in those studies, which ranged from 25 to 35 mg/mL, as being lower than the amount used to prepare the paste-like TAP (50 mg/mL).…”
Section: New Alternatives In the Concept Antibiotic-eluting Fibers Asmentioning
confidence: 99%
“…Although intracanal placement of antibiotic pastes has been well-accepted in regenerative endodontic protocols and is recommended by the American Association of Endodontists (AAE), the use of triple antibiotic paste (TAP) has been associated with undesirable clinical outcomes, because it interferes with the release of dentin growth factors 15 , inhibits vascularization due to the presence of minocycline (MINO) 16 , and high toxicity [13][14][15][17][18][19] . Moreover, TAP usually stains dentin 19,20 , causing crown discoloration; therefore, the AAE's current recommendation is that when using TAP as an intracanal medication, the professional should consider using low concentrations (eg, 1-5 mg/mL) of the antibiotics and/or apply TAP only after sealing the pulp chamber with a dentin bonding agent, thus minimizing the risk of staining 21 .…”
Section: Significancementioning
confidence: 99%
See 3 more Smart Citations